1977
DOI: 10.1507/endocrj1954.24.487
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotropic effects of cholera enterotoxin in the rat testis slices: Stimulation of adenylate cyclase activity and testosterone synthesis from cholesterol.

Abstract: SynopsisThe effects of cholera enterotoxin (CET) on the male gonad was investigated using testis slices of the rat.CET stimulated adenylate cyclase activity of the interstitial tissue of the rat testis, increased cyclic AMP (cAMP) production and testosterone release from the interstitial tissue in vitro, thus mimicking effects of LH and human chorionic gonadotropin (hCG). CET also stimulated adenylate cyclase activity of the seminiferous tubules and increased cAMP production, whereas hCG did not exhibit such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1979
1979
1979
1979

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…The present data of in vivo studies are quite consistent with our previous in vitro findings that CET stimulates adenylate cyclase/cyclic AMP system of testicular cells (probably of Leydig cells) and increases testosterone production (Sato et al, 1975(Sato et al, , 1977. Furthermore, we have demonstrated that a single intratesticular CET-injection persistently but not permanently stimulated the enzyme activity and caused the sustained elevation of serum testosterone concentration for at least3days, probably resulting in the stimulation of negative feedback mechanism of hypophyseal-testicular axis to suppress the LH release during these periods.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present data of in vivo studies are quite consistent with our previous in vitro findings that CET stimulates adenylate cyclase/cyclic AMP system of testicular cells (probably of Leydig cells) and increases testosterone production (Sato et al, 1975(Sato et al, , 1977. Furthermore, we have demonstrated that a single intratesticular CET-injection persistently but not permanently stimulated the enzyme activity and caused the sustained elevation of serum testosterone concentration for at least3days, probably resulting in the stimulation of negative feedback mechanism of hypophyseal-testicular axis to suppress the LH release during these periods.…”
Section: Discussionsupporting
confidence: 92%
“…Previously we reported that CET stimu lated adenylate cyclase activity of rat testis slices with a lag time of about30 min, caused an increase in cyclic AMP accumulation and stimulated testosterone synthesis from cholesterol in vitro, and suggested that these gonadotropic effects were exerted directly on Leydig cells (Sato et al, 1975;Sato and Ohsawa, 1977). This assumption was recently confirmed by Cooke et al,(1977) using purified Leydig cells of rat testes.…”
mentioning
confidence: 70%